Relationship between visual and neurodevelopmental measures at 2 years with visual acuity and stereopsis at 4.5 years in children born at risk of neonatal hypoglycaemia. (8th November 2021) - Paudel, Nabin; Thompson, Benjamin; Chakraborty, Arijit; Harding, Jane; Jacobs, Robert J; Wouldes, Trecia A; Yu, Sandy TY; Anstice, Nicola S; ,
Abstract: Purpose: Mild to moderate vision loss affects many children and can negatively impact a child's early literacy and academic achievement. Nevertheless, there is no consensus on which factors present in early childhood indicate the need for long‐term ophthalmic follow up, particularly in children with a history of perinatal adversity. This study identified the relationship between visual, cognitive, motor and demographic factors at 2 years of age and visual acuity (VA) and stereoacuity at 4.5 years of age. Methods: Five hundred sixteen children identified as being at risk of neonatal hypoglycaemia were recruited soon after birth. At 2 years of age, binocular VA, stereoacuity and non‐cycloplegic refraction were measured and a clinical neuro‐developmental assessment with the Bayley Scales of Infant Development III (BSID‐III) was conducted by a trained examiner. Monocular VA and stereoacuity were measured at 4.5 years of age. Results: Three hundred twenty‐eight children completed both the 2 and 4.5 year vision and neurodevelopmental assessments. Multiple linear regression showed oblique astigmatism and motor function at 2 years were significantly associated with VA at 4.5 years of age, while spherical equivalent refraction, motor scores and stereoacuity at 2 years were significantly associated with stereoacuity at 4.5 years of age. BSID‐III motor scores had the best sensitivity (81.8%) and specificity (51.5%) for identifying impaired stereoacuity at 4.5 years. However, all measures at 2 years were poorly associated with VA at 4.5 years old. Conclusion: Vision and neurodevelopmental measures at 2 years were poorly associated with visual function at 4.5 years of age. However, lower scores on tests of motor function at 2 years may be associated with vision abnormalities, particularly reduced stereopsis, at 4.5 years of age and referral for comprehensive vision assessment for these children may be warranted.